Radon interventions around the globe: A systematic review. Issue 5 (May 2019) - Khan, Selim M.; Gomes, James; Krewski, Daniel R.
Abstract: Background: Radon is the primary source of environmental radiation exposure posing a significant human health risk in cold countries. In Canada, most provinces have revised building codes by 2017, requiring construction solutions to avoid radon in all new buildings. While various construction solutions and remediation techniques have been proposed and evaluated, the question about the best method that would effectively reduce radon in a variety of contexts remained unanswered. Radon practitioners, officials of radon control programs, and businesses offering radon testing and mitigation services, builders, property managers, homeowners and residents also have similar queries. Objective: This paper systematically reviewed both experimental and observational studies (S) with radon interventions (I) used globally in residential houses (P) compared to other residential or model houses (C) to evaluate relative mitigation effectiveness (O) that could guide selecting the best radon reduction strategy for residential buildings. Methods: Two researchers searched fifteen academic bibliographic and grey literature databases for radon intervention studies conducted around the world, with particular emphasis on areas of North America and Europe published from 1990 to 2018. Interventions in residential and model houses were included, but studies piloted purely in the lab were excluded; the PRISMA checklist was used to synthesize data; Cochrane and Hamilton tools were used to evaluate study quality. Results: Studies around the globe have investigated a variety of construction solutions, radon mitigation and remediation systems with different levels of effectiveness. In most cases, sub-slab or sump depressurization system (SSDS) with active ventilation technique was found more effective in achieving a significant and sustained radon reduction than the passive methods such as sealing, membrane, block and beam, simple ventilation, or filtration. The choice of an optimal strategy largely depends on the factors related to the initial radon level, routes of entry, building design and age, as well as other geologic, atmospheric, and climatic conditions. Conclusion: Although an active SSDS is the best mitigation systems, at places, it needs to be combined with another system and installed by a trained radon professional considering the pertinent factors to ensure radon level continues to remain below the action level. This study did not conduct any economic evaluation of the mitigation measures. Future review with studies on the implementation of new building codes will provide updated evidence. Recommendation: For the practical implementation of radon mitigation, training of the construction industry, information provision for residents, the establishment of public funds, incorporation of radon-prone areas in the land utilization maps, and enacting building codes deemed essential.